Pemanfaatan Tumbuhan Obat Pada Masyarakat Suku Dayak Jangkang Tanjung Di Desa Ribau Kecamatan Kapuas Kabupaten Sanggau - Irwan Lovadi, Almida Sari, Riza Linda (Universitas Tanjungpura, 2015)
West Kalimantan is rich with various kinds of plants that can serve as medicine and the province is inhabited by various tribes. The largest tribe in Kalimantan is the Dayak. One of the tribes found in West Kalimantan is the Jangkang Tanjung Dayak who still use traditional medicine. This research aims to identify the types, parts and the preparation method of plants used as medicine by the Jangkang Tanjung Dayak Tribe in Ribau Village. The research was carried out from September to November 2014 in Ribau Village, Kapuas Sub-district, Sanggau Regency, West Kalimantan, and at the Biology Laboratory of the Faculty of Mathematics and Natural Sciences, University of Tanjungpura Pontianak by using the snowball method and semi-structured interviews. The results of the research discovered 65 species of medicinal plants belonging to 38 families. The most widely used family is the Euphorbiaceae, i.e. as many as 7 species. The most widely used parts of the plant is the leaf, i.e. 50% .The most widely used preparation method is boiling i.e. 48.59%. The habitat of medicinal plants found in the vicinity of the forest is at a percentage of 44.68%.